Disturbance Ecology in the Anthropocene - Newman, Erica A. (Frontiers in Ecology and Evolution, 2019)
With the accumulating evidence of changing disturbance regimes becoming increasingly obvious, there is potential for disturbance ecology to become the most valuable lens through which climate-related disturbance events are interpreted. In this paper, I revisit some of the central themes of disturbance ecology and argue that the knowledge established in the field of disturbance ecology continues to be relevant to ecosystem management, even with rapid changes to disturbance regimes and changing disturbance types in local ecosystems. Disturbance ecology has been tremendously successful over the past several decades at elucidating the interactions between disturbances, biodiversity, and ecosystems, and this knowledge can be leveraged in different contexts. Primarily, management in changing and uncertain conditions should be focused primarily on the long-term persistence of that native biodiversity which has evolved within the local disturbance regime, and is likely to go extinct with rapid changes to disturbance intensity, frequency, and type. Where possible, conserving aspects of natural disturbance regimes will be vital to preserving functioning ecosystems and to that native biodiversity that requires disturbance for its continued existence, though these situations may become more limited over time. Finally, scientists must actively propose management policies that incorporates knowledge of disturbance ecology. Successful policies regarding changing disturbance regimes for biodiversity will not merely be reactive, and will recognize that for natural ecosystems as for human society, not all desired outcomes are simultaneously possible.